PENINGKATAN HASIL BELAJAR BAHASA JERMAN MELALUI PENERAPAN MODEL PEMBELAJARAN POWER OF TWO - Girsang, Frida Br. (JURNAL PENA EDUKASI, 2019)
Abstract: Student learning outcomes by applying the Power Two learning model are increasing. Before the class action was carried out the average value of German language subjects for students in class XI was 60.01 with a standard deviation of 12.80. After taking action on the first cycle the average student learning outcomes value becomes 71.50 and the standard deviation is 7.25. Similarly in the second cycle the average student learning outcomes increased, which was 80.07 in the good category with a standard deviation of 7.21. Before the average category of action was carried out the student learning outcomes were in the low category with a completeness level of 37.5% (out of 40 students there were 15 people who completed). In the first cycle after the action was taken the student learning outcomes were in the medium category with an completeness level of 85% (34 people completed from 40 students). In the second cycle after further action was taken as a result of reflection the first cycle of student learning outcomes was in the high category (average value 80.07) with a percentage of completeness of 97.5%. Keywords: Learning Outcomes, Power Of Two Learning Model Abstrak: Hasil belajar siswa dengan menerapkan model pembelajaran Power Two menjadi meningkat. Sebelum dilaksanakan tindakan kelas nilai rata-rata mata pelajaran Bahasa Jerman siswa di kelas XI adalah 60,01 dengan simpangan baku 12,80. Setelah dilakukan tindakan pada siklus I nilai hasil belajar siswa rata-ratanya menjadi 71,50 dan standar deviasi 7,25. Demikian pula pada siklus II rata-rata hasil belajar siswa terjadi peningkatan, yaitu 80,07 berada pada kategori baik dengan simpangan bakunya 7,21. Sebelum dilakukan tindakan kategori rata-rata hasil belajar siswa berada pada kategori rendah dengan tingkat ketuntasan 37,5 % (Dari 40 orang siswa ada 15 orang yang tuntas). Pada siklus I setelah dilakukan tindakan hasil belajar siswa berada pada kategori sedang dengan tingkat ketuntasan 85 % (34 orang yang tuntas dari 40 siswa). Pada siklus II setelah dilaksanakan tindakan lebih lanjut sebagai hasil dari refleksi siklus I hasil belajar siswa berada pada kategori tinggi (nilai rata-rata 80,07) dengan presentase tingkat ketuntasan 97,5 %. Kata kunci: Hasil Belajar, Model Pembelajaran Power Of Two